Design and validation of a next generation sequencing assay for hereditary BRCA1 and BRCA2 mutation testing - Kang, Hyunseok P.; Maguire, Jared R.; Chu, Clement S.; Haque, Imran S.; Lai, Henry; Mar-Heyming, Rebecca; Ready, Kaylene; Vysotskaia, Valentina S.; Evans, Eric A. (PeerJ, 2016)
Hereditary breast and ovarian cancer syndrome, caused by a germline pathogenic variant in the BRCA1 or BRCA2 (BRCA1/2) genes, is characterized by an increased risk for breast, ovarian, pancreatic and other cancers. Identification of those who have a BRCA1/2 mutation is important so that they can take advantage of genetic counseling, screening, and potentially life-saving prevention strategies. We describe the design and analytic validation of the Counsyl Inherited Cancer Screen, a next-generation-sequencing-based test to detect pathogenic variation in the BRCA1 and BRCA2 genes. We demonstrate that the test is capable of detecting single-nucleotide variants (SNVs), short insertions and deletions (indels), and copy-number variants (CNVs, also known as large rearrangements) with zero errors over a 114-sample validation set consisting of samples from cell lines and deidentified patient samples, including 36 samples with BRCA1/2pathogenic germline mutations.
Keywords: Hereditary breast and ovarian cancer; BRCA testing; Next generation sequencing assay; Analytical validation